2013
DOI: 10.1080/13548506.2013.845303
|View full text |Cite
|
Sign up to set email alerts
|

Depression among patients with end-stage renal disease in hemodialysis

Abstract: Depression is frequent in end-stage renal disease (ESRD) and predicts mortality in dialysis patients. The aim of this study was to investigate the occurrence of depression among patients on hemodialysis. We conducted an observational cross-sectional study at two hemodialysis centres in the metropolitan area of Fortaleza, Ceará, Brazil, between September and October 2010. The occurrence of depression was evaluated according to Beck Depression Inventory II. Among 148 patients interviewed, the mean age was 46 ± 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
4
1
1
Order By: Relevance
“…4 A study found frequencies of severity of depressive symptoms in patients who were having hemodialysis between 19% and 68%. 5 Another study from Nigeria 6 with the patients (N=118) with CKD proved development of depressive symptoms as 34.5% in patients who were on qualitative analysis as compared to the patients who were not receiving dialysis patients (13.3%). During a study conducted in urban center, Brazil, patients with CKD (N=170), Andrade and Sesso 7 found a rather higher frequency of depressive symptoms among patients in qualitative analysis (41.6%), compared to patients underneath conservative treatment (37.3%).…”
Section: Introductionmentioning
confidence: 99%
“…4 A study found frequencies of severity of depressive symptoms in patients who were having hemodialysis between 19% and 68%. 5 Another study from Nigeria 6 with the patients (N=118) with CKD proved development of depressive symptoms as 34.5% in patients who were on qualitative analysis as compared to the patients who were not receiving dialysis patients (13.3%). During a study conducted in urban center, Brazil, patients with CKD (N=170), Andrade and Sesso 7 found a rather higher frequency of depressive symptoms among patients in qualitative analysis (41.6%), compared to patients underneath conservative treatment (37.3%).…”
Section: Introductionmentioning
confidence: 99%
“…AlDukhayel [ 19 ] carried out a study in Riyadh city in a single center and reported a high depression prevalence among PD and HD patients, at 98.5% and 83.5%, respectively. In India, in a single center, the researcher reported varying degrees of HD patient depression prevalence, e.g., 61% [ 20 ], 68% for two centers in Brazil [ 21 ], and a relatively lower rate of 23.3%, the results from two centers in Makkah, Saudi Arabia [ 22 ]. In Panama, a single center data reported 21.1% anxiety among such patients.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common psychological problem on hemodialysis patients. A research by Silva Junior et al [8] that investigate the occurrence of depression in 148 hemodialysis patients showed depression symptoms in 101 (68.2%) cases, being mild (49.5%), moderate (41.5%) and severe (9%). 15.5% participants had an earlier depression diagnosis.…”
Section: IIImentioning
confidence: 99%